A Meta-Analysis of MiRNA-497 and Prognosis of Hepatocellular Carcinoma - Zhiqiang Xie; Qingzhi Hao; Rongrong Zhu; Ruiping Ma (Canadian Journal of Gastroenterology and Hepatology)
Background. Recently, microRNA-497 (miR-497) has been reported as a prognostic marker for hepatocellular carcinoma (HCC). However, there is no systematic study summarizing these data. Herein, we elucidated the prognostic role of miR497 in HCC by using meta-analysis. Methods. We systematically searched Embase, PubMed, Web of Science, and, China National Knowledge Infrastructure for relevant studies. The two researchers conducted data extraction and quality evaluation independently. We used hazard ratios (HRs), odds ratios (ORs), and their 95% confidence interval (95% CI) to evaluate the relationship between miR-497 expression level and HCC prognosis. Results. A total of 6 studies involving 457 participants were included in this meta-analysis. There was a significant association between the lower level of miR-497 expression and the shorter overall survival (HR = 2.17, 95% CI: 1.67–2.84, P<0.001). Meanwhile, patients with low miR-497 expression were more prone to vascular infiltration (OR = 2.73, 95%: 1.79–4.17, P<0.001). However, the lower expression level of miR-497 had no significant correlation with TNM (tumor-node-metastasis) stage (OR = 1.47, 95% CI: 0.17–12.49, P=0.47). Conclusions. MiR-497 might serve as a prognostic biomarker in HCC, but more clinical studies are needed to confirm this view.